Financial expert witness communication : a practical guide to reporting and testimony - Preber, Bradley J. (John Wiley & Sons, 2014)
"The book provides practical guidance on financial forensic expert witnessing for reporting and testimony required in litigation from the standpoint of the expert witness. The focus is on accounting, financial forensics, forensic technology and damages experts who expect to be formally designated as an expert witness. Chapters written by nationally recognized experts include litigation and dispute resolution process, roles for the financial expert witness, retention, responsibilities of the expert witness, privilege, ethics, opinions, litigation reporting, testimony, ADR reporting communicating, the internet, and social media and the financial expert witness"--